Akibat Hukum Perkawinan Antar Agama Menurut Hukum Nasional Indonesia - Jamil, Jamil (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2015)
Measuring the religious and cultural diversity, was no longer present context to question the legal status of marriage between religions in Indonesia. Who need to know is about the legal consequences? Therefore, the problem discussed in this paper is whether the legal consequences arising from a marriage between religions in Indonesia’s national marriage law? By using normativ-analysis approach, the goal of this study is to critically examine the legal consequences of intermarriage in the Indonesian national marriage law.